Characteristics of Vernacular Architecture Malay Deli Traditional House Based on Technical Aspects of Building Structure - Novrial; Nila Rahmaini Siregar (International Journal of Architecture and Urbanism, 2021)
Local wisdom in an architectural context is part of cultural heritage, passed down from generation to the next generation and gone through a long process of gaining community recognition as a reflection of the region's culture, also known as vernacular architecture. Vernacular architecture can be found in almost every region, as is the city of Medan. Medan city is famous for its culture, especially its Malay culture, formed by the Sultan of Deli's influence so that Malay Deli emerged. In its formation, aspects of the creation of vernacular architecture also influenced the development of Malay Deli, mainly traditional houses. These traditional houses is visible from one of its forming aspects in the form of technical aspects such as building structure systems. This study discusses the characteristic of system structure in the Malay Deli traditional house and aims to identify and examine these problems. This study adopted a qualitative descriptive method approach to collect and analyze data so that the results obtained in the form of technical aspects of the structure of vernacular building structures from traditional Malay. This study's findings are a reference source for traditional Malay houses' vernacular architecture, specifically Malay deli or design considerations.